PENGARUH PEMBIAYAAN PEMILIKAN RUMAH GRIYA HASANAH TERHADAP KEPUASAN NASABAH DI BANK SYARIAH INDONESIA (BSI) KANTOR CABANG PEMBANTU PADALARANG - Tahsa; Tunggara, Imam; Ismiyanti, Nina (Jurnal Pelita Nusa, 2024)
Customer satisfaction is a feeling of happiness or disappointment experienced by a person with the goods or services provided, by comparing the suitability of the product received with the customer's expectations. This study aims to find out and analyze the influence of Griya Hasanah mortgage financing on customer satisfaction at BSI KCP Padalarang. In 2021, the number of customers using Griya Hasanah financing is still limited, because that year was the beginning of the merger of the previous three banks into BSI, so many programs have not been delivered to customers. The research method used is a quantitative method with a survey approach using a questionnaire. The population of this study is 51 people, with sampling covering the entire population. The results of the study show that the R Square value is 0.731 or 73.1%, which means that the financing of Griya Hasanah Mortgage (X) has a significant effect on customer satisfaction (Y) of 73.1%, and is included in the strong category. The remaining 26.9% was influenced by other variables outside of this model. Quantitative data showed that the correlation between the Griya Hasanah mortgage financing variable and customer satisfaction had a calculated value of 0.855 which was greater than the table of 0.275, indicating a strong correlation. Therefore, it can be concluded that the better the quality of Griya Hasanah's mortgage financing, the higher customer satisfaction at BSI KCP Padalarang.